Market Entry and Distribution Strategy for Interbev UK Ltd in Malaysia & Singapore - Sheikh, Omar (2013)
For UK export companies distributing branded alcoholic beverages globally, the opportunities posed by new growth markets such as those in South East Asia are particularly attractive. With emerging economies supporting growth and rising living standards, consumer buying habits have changed from the simple need for sustenance to sophistication. This has led to an overall increase in demand for luxury goods, especially those in the alcoholic beverage market. Two South East Asian countries in particular that have shown increasing demand in for alcoholic beverages are Malaysia and Singapore. Although relatively new countries having gained independence in only the last half-century, Malaysia and Singapore are very different markets and so pose a variety of considerations for any exporter looking to enter and distribute in these markets. This Management Project details recommendations as to the market entry and distribution strategy for a U.K. based alcoholic beverage exporter, Interbev UK Ltd, in Malaysia and Singapore. Using both primary and secondary sources of data, including conducting interviews with key stakeholders in the alcoholic beverage industry in both Malaysia and Singapore, analysis is performed combining the findings with theoretical constructs of market entry and distribution. Recommendations are given to Interbev UK Ltd for a separate mode of market entry for each country in the form of a 3-phase, 3-year market entry and distribution plan. The plan takes advantage of Singapore’s high re-export market and Malaysia’s attractive domestic market as well as being based on risk avoidance, minimal initial investment and organic growth. A major limitation has been a lack of financial data to support the recommendations with cash flow forecasts. Consequently this, along with other recommendations for further study has also been presented.